2017
DOI: 10.3390/su9020161
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Planning for Sustainability in Canadian Higher Education

Abstract: This paper reviews representations of sustainability in the strategic plans of Canadian higher education institutions (HEIs). A content analysis of the strategic plans of 50 HEIs was undertaken to determine the extent to which sustainability is included as a significant policy priority in the plans, including across the five domains of governance, education, campus operations, research, and community outreach. We found 41 strategic plans with some discussion of sustainability, and identified three characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…In this respect, they had a strong commitment to AASHE considering the autonomy in academia. The results of this study coincide with the proposal of Bieler and McKenzie [38], that to transform sustainability into higher education, the inclusion of variables related to policy, governance, education, campus operations, research and community outreach must include all stakeholders, including non-governmental organizations (NGOs), mentioned by Calder and Clugston [7].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this respect, they had a strong commitment to AASHE considering the autonomy in academia. The results of this study coincide with the proposal of Bieler and McKenzie [38], that to transform sustainability into higher education, the inclusion of variables related to policy, governance, education, campus operations, research and community outreach must include all stakeholders, including non-governmental organizations (NGOs), mentioned by Calder and Clugston [7].…”
Section: Discussionsupporting
confidence: 85%
“…Bieler and McKenzie [38] completed a study in Canadian HEIs. Their result focused on accommodative responses that addressed sustainability in one or two domains connected with the institution's management strategies and core values.…”
Section: Discussionmentioning
confidence: 99%
“…Determining community outreach is generally perceived as a difficult task [50,51]. The analysis of impacts on social behavior requires a more detailed proceeding which enables an in-depth analysis.…”
Section: Content Analysismentioning
confidence: 99%
“…In terms of organizational responsibility, major targets include issuing holistic approaches fostering quality management or society outreach to satisfy stakeholder needs and tackle social problems [19,50]. As there is a lack of mission statements embracing responsibility issues [53,54], the use of blanket statements [51] fostering the public image of the organization [53] suggests the need for more responsible management. The evolution of mission statements simultaneously calls for an investigation of managerial processes [55] to achieve better governance and leadership [48].…”
Section: Content Analysismentioning
confidence: 99%
“…Studies have shown that parents' educational attainment is closely related to children's academic success and educational level [19,20]. Parents with higher educational attainment feel more capable of helping their children, are more aware of academic performance, and are more prone to monitoring their children's academic progress [21].…”
Section: Parents' Educational Attainmentmentioning
confidence: 99%